Algorithm for early detection of a high risk of speech sound disorders in children - Grudziąż-Sękowska, Justyna; Olczak-Kowalczyk, Dorota; Zadurska, Małgorzata (Forum Ortodontyczne / Orthodontic Forum, 2018)
Anatomical defects and functional disorders of the masticatory system are often accompanied by speech sound disorders. Speech therapy prophylaxis, as well as prevention of disorders of all parts of the masticatory system, is focused on monitoring of the proper development of anatomy and functions typical of a given developmental period. An early therapeutic intervention is associated with better results. Aim. This study aimed to create a simple tool for dentists to assess the risk of articulation disorders using several preselected physical and functional characteristics. Materials and methods. Three hundred children aged 7-10 years had a dental and speech examination performed. Using the CHAID algorithm upon assessing the disorders of the masticatory system and coexisting speech sound disorders, it was possible to create a decision tree to determine the probability of two disorders occurring at the same time. Results. It was observed that there were many correlations between individual anatomical or functional disorders and presence of speech sound disorders. The strength of those correlations was measured. Mesioclusions, distoclusions, open bites, short lingual frenulum, persistent infantile swallow pattern, mouth breathing, and premature loss of deciduous teeth were all determined to increase the risk of speech sound disorders in children. Conclusions. This algorithm is a simple diagnostic tool for dentists. It enables early detection of a high risk of speech sound disorders. Children with particular malocclusions should undergo speech therapy prophylaxis and be referred to consultations with a speech therapist. Early detection of such abnormalities will allow to avoid not only the intensification and consolidation of speech defects, but also certain pathologies of the oral cavity. (Grudziąż-Sękowska J, Olczak-Kowalczyk D, Zadurska M. Algorithm for early detection of a high risk of speech sound disorders in children. Orthod Forum 2018; 14: 119-29).